2017
DOI: 10.1103/physreve.96.012149
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniversality in the erosion of tilted landscapes

Abstract: The anisotropic model for landscapes erosion proposed by Pastor-Satorras and Rothman in [R. Pastor-Satorras and D. H. Rothman, Phys. Rev. Lett. 80, 4349 (1998)] is believed to capture the physics of erosion at intermediate length scale ( 3 km), and to account for the large value of the roughness exponent α observed in real data at this scale. Our study of this modelconducted using the nonperturbative renormalization group (NPRG) -concludes on the nonuniversality of this exponent because of the existence of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 69 publications
(121 reference statements)
1
33
0
Order By: Relevance
“…This result is not surprising if we remember that the upper critical dimension for the white noise is d * = 2. Indeed, the model would only predict trivial scaling in its upper critical dimension, the fact that was confirmed in [3]. The spatially quenched disorder, however, yields upper critical dimension d * = 4.…”
Section: Static Approach To Rg Analysis Of the Pastor-satorras-rothmamentioning
confidence: 87%
See 4 more Smart Citations
“…This result is not surprising if we remember that the upper critical dimension for the white noise is d * = 2. Indeed, the model would only predict trivial scaling in its upper critical dimension, the fact that was confirmed in [3]. The spatially quenched disorder, however, yields upper critical dimension d * = 4.…”
Section: Static Approach To Rg Analysis Of the Pastor-satorras-rothmamentioning
confidence: 87%
“…One way to study scaling behavior of a fluctuating surface is to describe the system by stochastic differential equation for the height field h(x) subjected to a random force f (x) where x = {t, x} and x is the spatial coordinates at the moment t. Recently it was shown that the choice of this random force (or noise) can dramatically affect the scaling behavior. Precisely, the choice of the quenched disorder in the Pastor-Satorras-Rothman model of a landscape erosion [1,2] proved to be the decisive factor leading to a type of scaling that explained previously thought inconclusive experimental data [3].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations